2016
DOI: 10.1136/bmjopen-2015-008795
|View full text |Cite
|
Sign up to set email alerts
|

Can HIV reverse transcriptase activity assay be a low-cost alternative for viral load monitoring in resource-limited settings?

Abstract: ObjectiveTo evaluate the performance and cost of an HIV reverse transcriptase-enzyme activity (HIV-RT) assay in comparison to an HIV-1 RNA assay for routine viral load monitoring in resource limited settings.DesignA cohort-based longitudinal study.SettingTwo antiretroviral therapy (ART) centres in Karnataka state, South India, providing treatment under the Indian AIDS control programme.ParticipantsA cohort of 327 HIV-1-infected Indian adult patients initiating first-line ART.Outcome measuresPerformance and cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Patients who did not respond to ART during the 36 month follow up were classified as having TF. In accordance with the World Health Organization (WHO) guidelines, and with other studies, TF was defined as viral load > 5,000 copies/mL . In contrast, controls were identified as patients who did respond to treatment and who did not meet the criteria for TF; these patients were classified as having TS.…”
Section: Methodssupporting
confidence: 89%
“…Patients who did not respond to ART during the 36 month follow up were classified as having TF. In accordance with the World Health Organization (WHO) guidelines, and with other studies, TF was defined as viral load > 5,000 copies/mL . In contrast, controls were identified as patients who did respond to treatment and who did not meet the criteria for TF; these patients were classified as having TS.…”
Section: Methodssupporting
confidence: 89%
“…However, later reports showed no association between the presence of RT inhibitors or resistance mutations with differences between RT activity and HIV-1 RNA in the plasma (23,29,32,57,58). Although our study was not designed to investigate the effect of RT inhibitors on the performance of ExaVir Load in HIV-2 infection, our results agree with these reports since no significant differences were found between viral load measurements with ExaVir Load or qPCR in treated and untreated patients.…”
Section: Discussionsupporting
confidence: 78%
“…A systematic underestimation of 0.3 log 10 copies/ml was also reported for ExaVir Load version 3 in aliquots of a World Health Organization international standard of HIV-1 subtype B (30). Greengrass et al compared ExaVir Load version 3 with Roche Cobas HIV-1 Monitor test and found a disagreement of Ͼ0.5 log 10 copies/ml in 27% of samples collected from HIV-1-infected individuals (32); this percentage was 18% when Gupta et al compared ExaVir Load version 3 to Abbot m2000rt (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations